Corporate entrepreneurial orientation and the performance of the Sabah state government link companies - Gary Albert Jimbih (2008)
This study aims to determine the relationship existed between the various factors dictating the corporate entrepreneurial orientation and the performance of the Sabah State Government Unk Companies (GLCs). The main objectives of the study was to determine the relationship between the performance of the Sabah state GlCs in relation to the internal environment for corporate entrepreneurship (managerial support, work discretion, rewards, time availability, organizational boundaries), organizational factors (age of firm, size of firm) and the external factors (technological changes). Data collection was conducted through questionnaire and interviews and a total of 35 respondents had participated in the research process. The results from the analysis obtained from the data collected shows that 41.8% of the variance are able to be explained by the research model. Managerial support, rewards and organizational boundaries produces a significant result while others appear to be insignificant. Further research is still need to be done in relation to the development of the state government link companies and the incorporation of the values of corporate entrepreneurship in their business activities to enable all the GLCs to prosper and further contribute to the development of the nation and the state of Sabah in particular.